Farming Approaches to Non-Agroecological Onion Production in Grand-Popo, South-West Benin - Togbe, Codjo Timothée; Sessou, Koffi Eric; Tchekessi , Célestin Kintomagnimessè Comlan (Journal of Ecohumanism, 2025)
In the Grand-Popo commune in Benin, non-agroecological onion production practices are observed. Despite warnings about health and environmental risks, this persistent and mobilizing cultural option of chemical inputs raises scientific curiosity. Assuming that non-agroecological onion production practices are based on farming approaches, this research aims to analyze them. To achieve this, semi-structured individual interviews and direct observation were used. Through reasoned choice, 25 actors were interviewed following diversification and saturation. Processed through triangulation and content analysis, the empirical data were compared with the theories of rational choice and social representations. The results reveal that the minimal use of biological inputs and maximal use of chemical fertilizers and pesticides are underpinned by several farming approaches: soil fertilization, crop protection and yield increasing. Even though these farming approaches are relevant, the main government is called upon to develop and implement agricultural policies that minimize the abusive use of chemical inputs in food production.